SYNCHRONIZATION OF COPYRIGHT ACT WITH BROADCASTING ACT (A LEGAL COMPARATIVE STUDY WITH NORMATIVE APPROACH) - Abdullah Husain; Runtung Sitepu; OK. Saidin; Keizerina Devi (USU LAW JOURNAL, 2017)
ABSTRACT The present sophisticated information needed by the people  has been taken advantage by the mass media whose roles are to pass some information, educate, express some opinions, and share knowledge to their readers and audiences. In order to fulfill the people’s needs, the mass media are always active to produce quick, actual and original information. Broadcasting agency, as the media of communication for news broadcasting, is legally protected to broadcast voices or images which are the results of copyright work to the public. The research method applied is normative legal research method carried out through studies on relevant laws and legal materials and supported by collecting related information.  The data are collected through library study and qualitatively analyzed. The results show that copyright and broadcasting are the activities that will always intersect with the intellectual property and copyright which can be seen in Article 1 number 8 of the Law No. 28/2014 concerning Copyright that particularly discusses about broadcasting agency. Article 63 of the Law No. 28/2014 concerning Copyrights also mentions that the time length of the protection validity by Neighboring Rights is: a. valid for 50 (fifty) years for the Show Actors, since the show was recorded in Phonogram or audiovisual; b. valid for 50 (fifty) years for the Phonogram Producer since the Phonogram was fixed; and c. valid for 20 (twenty) years for the Broadcasting Agency since its broadcast work was aired for the first time. The role of the Broadcasting Commission of Indonesia as the people’s representative is to uphold the law, in particular, to implement the administrative sanction. It is also expected that the people be able to take part in establishing the healthy broadcasting morality. The media must be improved to strengthen the people to be more educated. It is also expected that with the high media awareness, the public can control and supervise the television broadcastings.   Keywords: Copyright, Broadcasting, Synchronization